Performance : live art since 1960. - Anderson, Laurie; Carlos, Laurie; Goldberg, RoseLee (New York : Harry N. Abrams Inc. Publishers, 1998)
Live performance is now one of the dominant art forms worldwide. In the United States and Europe, Japan, India , and Africa, an ever-increasing number of artists, including Robert Wilson, Marina Abramovic, Pina Bausch, Karen Finley, and Matthew Barney, in a variety of styles, are engaged in evocative, contemplative, and critical performance works. This is the most complete and profusely illustrated survey of performance from the 1960s to the present. RoseLee Goldberg, the acknowledged authority on performance art and author of Abrams' 1979 Performance : Live Art 1909 To The Present, begins her discussion with the emergence of performance in the work of Yves Klein and Piero Manzoni and later in that of Meredith Monk and Laurie Anderson. In words and stunning photographs she shows how performance explores and reveals the unexpected and the forbidden more than any other art form. This exciting volume features sections on politics, theater, music, and opera ; the body ; identity ; feminism and multiculturalism ; new dance ; the spoken word ; video ; rock and roll ; and much more. Artists' biographies, a chronology, and a bibliography are included in the invaluable reference section. Performance breaks the barriers separating art and life, private and public, custom and taboo. Here, Goldberg demonstrates the depth and breath of performance and its profound impact on every other form of contemporary art.
Abdoh, Rezah ; Abramovic, Marina ; Acconci, Vito ; Act-Up ; Adams, John ; Alien Comic (Tom Murrin) ; Anderson, Laurie ; Antin, Eleanor ; Antoni, Janine ; Apple, Jacki ; Arcade, Penny ; Arias, Joey ; Armitage, Karole ; Ashley, Robert ; Athey, Ron ; Bag, Alex ; Baker, Bobby ; Barney, Matthew ; Bausch, Pina ; Bean, Anne ; Beecroft, Vanessa ; Ben ; Beuys, Joseph ; Black Market International ; Bogosian, Eric ; Branca, Glenn ; Brisley, Stuart ; Brown, Trisha ; Bruguera, Tania ; Brus, Günter ; Burden, Chris ; Butoh ; Cage, John ; Cai Guo-Qiang ; Cale, David ; Carlos, Laurie ; Castellucci, Romeo ; Catling, Brian ; Chang, Patty ; Chicago, Judy ; Childs, Lucinda ; Colette ; Comfort, Jane ; Coum Transmissions ; Cunningham, Merce ; Dance for the Camera ; Dean, Laura ; Dine, Jim ; DJ Spooky (Paul D. Miller) ; DV8 Physical Theatre ; Eichelberger, Ethyl ; Elwes, Catherine ; English, Rose ; Eno, Brian ; Export, Valie ; Fabre, Jan ; Fagan, Garth ; Falso Movimento ; Feminist Art Workers ; Fenley, Moussa ; Finley, Karen ; Forced Entertainment Opera ; Foreman, Richard ; Forsythe, William ; Forti, Simone ; Fraser-Munro, Ronald ; Fusco, Coco ; Galas, Diamanda ; Garhel and Galindo ; Garrard, Rose ; Gaulke, Cheri ; Gilbert & George ; Glass, Philip ; Goebbels, Heiner ; Gomez-Pena, Guillermo ; Graham, Dan ; Grand Union ; Gray, Spalding ; Greenaway, Peter ; Grooms, Red ; Guerrilla Art Action Group (GAAG) ; Guerrilla Girls ; Gutai Group ; Halprin, Ann ; Hamilton, Ann ; Hatoum, Mona ; Heyward, Julia ; Hi Red Center ; Hoch, Danny ; Horn, Rebecca ; Hughes, Holly ; Jabowitz, Leslie ; Jesurun, John ; Jonas, Joan ; Jones, Bill T. ; Jones, Kim ; Julien, Isaac ; Kaprow, Allan ; De Keersmaeker, Anne Teresa ; Kelley, Mike ; Kelly, John ; Kelly, Mary ; Kids, Kipper ; Klein, Yves ; Knizak, Milan ; etc.
First published in Great Britain in 1998 by Thames and Hudson Ltd. London
Biog. p. 212-228, Bibliog. p. 229-231
Chronology : a select chronology of events in the history of performance since 1960 p. 208-212
List of illustrations p. 232-236
Engels
boek